Középiskolai tanárok digitális kompetenciája és annak alkalmazása az oktatásban - Hetyei Kornél (2019)
The aim of this paper is to analyse the level of competence among secondary school teachers and to examine how these competences are acquired in the planning and execution of teaching-learning processes, moreover, how they can advance efficient performance and successful teaching materiel processing. This research places emphasis on confirming or rejecting the 5 hypotheses. The research uses online survey and personal interview among local and online teachers which are inductive and exploratory and examine the existence of digital knowledge and the level of acquired skills. Additionally, they examine whether owned digital competence is an attitude or not. The hypotheses discuss the relationship between the depth of teachers’ knowledge and their occupational orientation, age, their motivation relating to using ICT (Information and Communications Technology) during lessons and their motivation relating to acquiring these necessary competences (accepting help, giving help, ICT further education) The results are diverse in case of some questions, the wide variety of the answers proves that the participants not only reveal the situation of a small number of people but also, they suggest generalisation. The topic of this research demonstrates a current issue in education and it urges to consider and carry out it.